2021
DOI: 10.1051/e3sconf/202132804018
|View full text |Cite
|
Sign up to set email alerts
|

Research trend on erbium-doped tellurite glasses based on scopus database

Abstract: This paper aims to analyse the research trend of erbium-doped tellurite glasses. To this aim, this paper applied bibliometric analysis. The comprehensive research document on the topic of erbium-doped tellurite glasses in the Scopus database is 695 documents. The result revealed that scientific publication on erbium-doped tellurite glasses has been increasing. China contributed the most documents on erbium-doped tellurite glasses. The visualization of the research trend on erbium-doped tellurite glasses assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The method is descriptive research. It used analysis of bibliometric based on Scopus data [12,[20][21][22]. The procedure of the research as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The method is descriptive research. It used analysis of bibliometric based on Scopus data [12,[20][21][22]. The procedure of the research as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is believed increasing the light optical absorption. Therefore, tellurite glasses doped by erbium were developed for application as an optical amplifier, a potential high-energy capacitor, a laser host, and the others [10][11][12][13]. There are various types of glass material compositions with a host of tellurium dioxide which is then doped with erbium ions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations